ANALYSIS OF THE IMPORTANCE OF IMPLEMENTING ETHNOSCIENCE-BASED LEARNING IN ELEMENTARY SCHOOLS FOR STUDENTS - Putri Monica Graciela Siahaan (CV Edukastra Mandiri, 2025)
Ethnoscience is an activity that transforms indigenous scientific practices consisting of knowledge derived from ancestral beliefs, which often still contain elements of myth. Ethnoscience-based learning serves as a bridge between students’ cultural backgrounds and scientific culture. In schools, it enables students to enhance the quality of their personal development as future generations of the nation. Through ethnoscience, learners are expected to optimize both the learning process and its application in daily life. The implementation of ethnoscience also fosters students’ critical thinking skills and encourages their active participation in exploring and appreciating their own cultural heritage. Moreover, ethnoscience can be identified through educational processes closely related to everyday life. The primary aim of this study is to examine how ethnoscience-based learning is implemented, particularly at the elementary school level, and how students are able to connect their cultural traditions with scientific inquiry.